Outdoor education: its relationships to outdoor recreation - Mohd Yasim, Mazuki; Aziz, Azlizam; Md Taff, Md Amin; Zakaria, Jaffry (2014)
There can often be confusion among practitioners about the relationship between outdoor education and outdoor recreation and how they relate to personal and social development. This article provides an overview of the relationship of both fields. Consequently, it is important for practitioners to understand and as an eye opener about the roots and its notions. The discussion hopefully will enlighten the issues of sceptical perception for both groups of practitioners' due to lack of understanding the notion, method, fundamental theoretical and objectives of each field.